Relasi Bonek dan Jawa Pos dalam Perspektif Strukturasi - Fajar Junaedi; Heru Nugroho; Sugeng Bayu Wahyono (Universitas Muhammadiyah Yogyakarta, 2017)
Jawa Pos is a regional newspaper from Surabaya that has successfully expanded its business to the national level as a national media conglomeration since the 1980s by developing sports journalism. Through sports journalism, Jawa Pos provides an affluent portion of news on Persebaya, a football club from Surabaya. Coinciding with an abundance of news section of Persebaya, Jawa Pos from the beginning made Persebaya fans known as Bonek as a newspaper consumer. The relations between Jawa Pos and Bonek is getting stronger when Jawa Pos holds Persebaya shares in 2017. Bonek is not only consumes as a reader of Jawa Pos newspaper, but also a consumer of match tickets and various Persebaya merchandise officially controlled by Jawa Pos. Although Jawa Pos is trying to build a structure that places Bonek as a consumer, the relationship between Jawa Pos and Bonek is not deterministic, but it develops dynamically. On the one hand, Java Post became a structure and Bonek became an agency whose relation was duality. In this relationship, Bonek is not only in a passive position, but also in an active position in their relationship with Jawa Pos. This Bonek and Jawa Pos relationship shows that Indonesian football fans are able to become an agency in the relations with club management.